Computer-aided classification of MRI for pathological complete response to neoadjuvant chemotherapy in breast cancer. - Yan, Shaolei; Peng, Haiyong; Yu, Qiujie; Chen, Xiaodan; Liu, Yue; Zhu, Ye; Chen, Kaige; Wang, Ping; Li, Yujiao; Zhang, Xiushi; Meng, Wei (Future Oncology, 2022)
Background: To determine suitable optimal classifiers and examine the general applicability of computer-aided classification to compare the differences between a computer-aided system and radiologists in predicting pathological complete response (pCR) from patients with breast cancer receiving neoadjuvant chemotherapy. Methods: We analyzed a total of 455 masses and used the U-Net network and ResNet to execute MRI segmentation and pCR classification. The diagnostic performance of radiologists, the computer-aided system and a combination of radiologists and computer-aided system were compared using receiver operating characteristic curve analysis. Results: The combination of radiologists and computer-aided system had the best performance for predicting pCR with an area under the curve (AUC) value of 0.899, significantly higher than that of radiologists alone (AUC: 0.700) and computer-aided system alone (AUC: 0.835). Conclusion: An automated classification system is feasible to predict the pCR to neoadjuvant chemotherapy in patients with breast cancer and can complement MRI.